Investigation and Analysis of Debris Flow Phenomenon - et. al., Amirhossein Mirdarsoltany, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The debris flows are one of the most dangerous types of landslides, which mostly occur suddenly and cause enormous losses. These flows are among the natural hazards of steep and mountainous areas around the world that are highly sedimentary. debris flow containing particles of clay, silt and Rubble, large trees or parts of buildings. this flow is movement by high velocities and it has highly destructive due to its high specific gravity and high sedimentary load (with 70 to 90 percent of the sedimentary load) and can carry very large and heavy rubble in the flow path. Factors affecting the formation of debris flows include: steep slopes, sparse vegetation cover, abundant rock with soft particles and fine-grained rocks, and sufficient and intermittent moisture. How the formation, fluid characteristics, type of sediment, sediment load, the calculation of discharge as well as control and damage of debris flow much different from floods. Unfortunately, in Iran, most of the time, experts are making a mistake in identifying these flows and behaving like floods with these flows. Therefore, it is important and necessary to know the characteristics of these types of flows. In this study, the phenomenon of debris flow has been studied and analyzed.